42nd AIAA Aerospace Sciences Meeting and Exhibit 2004
DOI: 10.2514/6.2004-267
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of High Speed Reacting Flows: Established Practices and Future Challenges

Abstract: Computational fluid dynamics (CFD) has proven to be an invaluable tool for the design and analysis of highspeed propulsion devices. Massively parallel computing, together with the maturation of robust CFD codes, has made it possible to perform simulations of complete engine flowpaths. Steady-state Reynolds-Averaged Navier-Stokes simulations are now routinely used in the scramjet engine development cycle to determine optimal fuel injector arrangements, investigate trends noted during testing, and extract variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 51 publications
1
40
0
Order By: Relevance
“…In the above given equations 17 to 20, ρ is the density, P is the pressure, u i is the velocity, E is the total energy which is equal to the sum of total internal energy and kinetic energy, H is total enthalpy which is equal to the sum of total internal energy and pressure-volume work, τ ij is the stress tensor, q j is the heat flux vector and X m , V j and m w  are mass fraction, mass diffusion velocity, and mass production rate, respectively of species "m" [84].…”
Section: Governing Equationsmentioning
confidence: 99%
“…In the above given equations 17 to 20, ρ is the density, P is the pressure, u i is the velocity, E is the total energy which is equal to the sum of total internal energy and kinetic energy, H is total enthalpy which is equal to the sum of total internal energy and pressure-volume work, τ ij is the stress tensor, q j is the heat flux vector and X m , V j and m w  are mass fraction, mass diffusion velocity, and mass production rate, respectively of species "m" [84].…”
Section: Governing Equationsmentioning
confidence: 99%
“…When combustion dynamics are added to the problem, uncertainty exists in the turbulence-chemistry interaction, shock wavechemistry interaction, as well as the general lack of adequate knowledge of the effects of supersonic conditions on turbulence, reaction rates, and flame regimes. Review of these problems can be found in [11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The required turbulence and combustion models have not significantly advanced in the past 20 years, and modelers must rely on experimental data and intuition to validate these phenomenological models. An excellent review of the modeled equations that are typically solved and the models needed to close the equations was given by Baurle [102]. The limitations introduced by the models have resulted in the move to higher-order modeling including LES and PDF methods.…”
Section: Hyper-x and A New Generation Of High-speed Reacting Flomentioning
confidence: 99%